ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEHIDUPAN ANAK PUNK - kumalasari, defi; Suberi, Moch; S, Tyas Farida; Koriyah, Koni'atul (Fakultas Ekonomi Universitas Gresik, 2018)
The punk children in Bojonegoro know that researchers are looking foractivities in order to make money to meet their own needs and enjoymentas punk children, for example, as street buskers at red lights. Based onthat knowledge the researcher is interested to do research about thefactors that influence the life of punk children. The method used in thisresearch is qualitative method with case study approach. Data collectiontechniques used are unstructured interviews, while the data analysistechniques we use is to write the results of interviews, reading, andunderstand the results of interviews. After understanding the researchersI will present in the discussion and then draw conclusions. The results ofresearch in this study are there are 3 factors that influence a persondecisions in making decisions to be punk children, the first is becausefriends, parents, and the environment. Furthermore, the reason why punkchildren live on the streets is because they want freedom, while on theirlifestyle is they like to follow the concert and earn money by singing.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475668